(untitled) (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
نفذ هذا البحث في مزرعة كلية الزراعة لدراسة تأثير 5 كثافات هي 8.30، 10.0، 12.5، 16.7، 25.0 نبات/م2 على نمو صنف الفول الدوماني، صممت التجربة بالطريقة العشوائية الكاملة في أربعة مكررات، بينت الدراسة النتائج الآتية: أدت زيادة الكثافة النباتية من 8.3 إلى 25 نبات/م2 إلى زيادة معنوية في المساحة النسبية للأوراق، ومعدل نمو المحصول والكفاءة التمثيلية خلال مرحلتي النمو 35 ـ 70 يوماً و 70 ـ 105 أيام. انخفض بالمقابل المسطح الورقي والمادة الجافة ومعدل النمو النسبي، وفترة بقاء الأوراق على كفاءتها خلال المرحلتين المذكورتين أعلاه، انخفض معدل المساحة النسبية للأوراق، ومعدل النمو النسبي عند جميع الكثافات خلال الفترة من 70 ـ 105 أيام بالمقارنة مع الفترة 35 ـ 70 يوماً، بينما ارتفع معدل نمو المحصول خلال الفترة 70 ـ 105 أيام بالمقارنة مع الفترة 35 ـ 70 يوماً بعد الزراعة خلال الموسمين. أعطت الكثافة 16.7 نبات/م2 أفضل القيم في الكفاءة التمثيلية خلال مرحلتي النمو بالمقارنة مع جميع الكثافات المدروسة. This research was carried out on the Faculty of Agriculture. Farm in order to study the density effect of 5 plants: 8.3, 10.0, 12.5, 16.7 and 25 plants/m2 on the growth of Domane variety faba bean. The experiment was randomly designed using 4 replicas. The results showed the following: increased plant density from 8.3 to 25 plants/m2 resulted in a significant increase in leaf area rate (LAR), and in crop growth rate (CGR) and net assimilation rate (NAR) during both stages of growth 35 – 70 and 70 – 105 days after planting. However, leaf area, weight of dry matter, relative growth rate (RCR), and leaf area duration (LAD decreased) during the above-mentioned stages. The leaf area rate (LAR) and relative growth rate (RGR) per all densities decreased during 70 – 105 day in comparison with 35 – 70 days after planting when the crop growth rate increased during 70 – 105 days compared with stages 35 – 70 days after planting during the two seasons. Compared to all studies plant densities, the density 16.7 plant/m2 gave a better value (NAR) during the two research seasons.